Faktor Yang Mempengaruhi Gairah Belajar Warga Belajar Program Kesetaraan Di PKBM Mitra Riau Jaya Cemerlang Kecamatan Marpoyan Damai Kota Pekanbaru - Nurfia Karnita; Aswandi Bahar; Widiastuti ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
This research aimed to understand the influence of the student learning passionfor the program equivalence of education at PKBM Riau Jaya, MarpoyanPekanbaru. The type of research is descriptive with quantitative approach. Thesamplewas the30 participants of the program equivalence at PKBM Mitra Jaya,with 3 programs: PAKET A = 7, PAKETt B = 11, and PAKET C = 12PARTICIPANT. To collect the data, the questionaire is used wit four alternativeunswers. Theresewarch indicators are divided into two parts; that are intrinsicsand extrinsicks. The result shows that the extrinsic aspects is more influencing tothe student learning passion rather than intrinsic aspect. As the whole, the resultdescribe that the student learning passion at the program equavalence of educationis pretty good.Key word:Study, The influence, passion learn.